Fluoride removal by Palm Kernel Shell Activated Carbon (PKSAC): batch and isotherms approach - Abu Bakar, Ayu Haslija; Yin, Shin Koay; Chuah Abdullah, Luqman; Choong, Thomas S Y; Al-Khatib, Ma'an Fahmi Rashid; Mobarekeh, Mohsen Nourouzi; Mohd Zahri, Nur Amirah; Yern, Chee Chin (2018)
Fluoride, which is classified as one of the contaminant of water for human consumption by the World Health Organisation (WHO) has been recognised as one of the serious problem worldwide by contaminating the groundwater. According to WHO, the standard prescribed for fluo1ide ion concentration in drinking water is 1.0 mg/l. Higher concentration of fluoride causes dental fluorosis (1.5-2.0mg/l) and skeletal fluorosis (>3.0mg/l). In this study. adsorption was chosen as fluoride removal method. A good adsorption system required an efficient adsorbent at an optimum condition. An agricultural waste, palm kernel shell (PKS) which is locally available as abundant material. in the form of activated carbon was used as the adsorbent for adsorbing fluoride from waste water. Characteristic of PKSAC was analysed using BET and SEM analysis. BET results showed pore type of PKSAC which consist of mesopores and SEM analysis showed the image of the pores. Effect of various factors on the fluoride removal was investigated such as pH. initial concentration, adsorbent dosage and contact time. Adsorption capacity increased with the increased of adsorbent dosage and contact time probably clue to the increase in the mass transfer driving force, resulting in a higher loading capacity for PKSAC. as its active sit.es were occupied by a larger amount of fluoride ions. Optimum parameters which resulted in maximum adsorption capacity of l.3mg/ g and fluoride removal of 38% was achieved at pH 4 with initial concentration of 20 mg/L. an adsorbent dosage of 4 g/ L with contact time of 4 h. The adsorption behavior was further investigated using equilibrium isotherms. Isotherms such as Langmuir, Freundlich, Redlich-Peterson and Temkin were studied which shown Redlich-Peterson fit well with a coefficient correlation (R2) of 0.99. These results suggest that palm kernel shell activated carbon (PKSAC) has the potential to serve as a good adsorbent for fluoride removal from aqueous solutions.